2018
DOI: 10.1002/ejic.201800109
|View full text |Cite
|
Sign up to set email alerts
|

As–N and As–N–P Cage Compounds Generated by [2+2] Addition of Diazenes and Diphosphenes to Diarsadiazanediyls

Abstract: The isolation of binary As–N and ternary As–N–P cage compounds consisting exclusively of group 15 elements was achieved by exploiting the reactivity of diarsadiazanediyl. This arsenic centered biradical is capable of activating and/or quenching small molecules bearing double bonds such as diazenes, Ph–N=N–Ph, or in situ generated labile diphosphenes, e.g. Ph–P=P–Ph, leading to the formation of hexapnicta‐[2.1.1]bicyclohexanes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“… In particular, our own group could demonstrate the versatile reactivity of the stable four-membered cyclic biradical [P­(μ-NR)] 2 ( 1 , R = Ter [2,6-dimesitylphenyl] or Hyp [tris­(trimethylsilyl)­silyl]), which is based solely on group 15 elements (Scheme ). …”
Section: Introductionmentioning
confidence: 99%
“… In particular, our own group could demonstrate the versatile reactivity of the stable four-membered cyclic biradical [P­(μ-NR)] 2 ( 1 , R = Ter [2,6-dimesitylphenyl] or Hyp [tris­(trimethylsilyl)­silyl]), which is based solely on group 15 elements (Scheme ). …”
Section: Introductionmentioning
confidence: 99%
“…[P(μ‐NTer)] 2 is a thermally very robust biradical which can be generated in very good yields by reducing [ClP(μ‐NTer)] 2 with magnesium turnings. With [P(μ‐NTer)] 2 in hands, we studied its reactivity towards molecules bearing single, double and triple bonds , , , . We also succeeded in preparing and isolate the arsenic homologue [As( μ ‐NTer)] 2 as well as the mixed arsenic–phosphorus‐centred biradical [P( μ ‐NTer) 2 As] .…”
Section: Introductionmentioning
confidence: 99%
“…With [P(μ-NTer)] 2 in hands, we studied its reactivity towards molecules bearing single, double and triple bonds. [46,47,[56][57][58][59][60][61][62][63][64][65]48,[66][67][68][69][70][71][49][50][51][52][53][54][55] We also succeeded in preparing and isolate the arsenic homologue [As(μ-NTer)] 2 [47] as well as the mixed arsenic-phosphorus-centred biradical [P(μ-NTer) 2 As]. [72] The reactivity of the biradical [E(μ-NTer)] 2 (E = P, As) towards small molecules like acetone, acetonitrile, CO, CO 2 , H 2 , alkenes and alkynes has been investigated extensively.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we have shown that pnictogen centered biradicaloids of the type [E(μ‐NR)] 2 (E = P, As, Sb, Bi; R = Ter, Hyp) can be generated and utilized for the activation of molecules bearing single, double and triple bonds. [ 48–51 ] While [E(μ‐NR)] 2 with E = P and As can be prepared in bulk, [ 51–54 ] the heavier congeners are only of fleeting existence in solution, [ 47 ] but once prepared in situ, they can also be used for the activation of small molecules. For example, [E(μ‐NR)] 2 (E = P, As, Sb, Bi; R = Ter) reacts readily with alkenes or alkynes forming [2.1.1]bicyclic structures (Scheme 3, product A ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, [E(μ‐NR)] 2 (E = P, As, Sb, Bi; R = Ter) reacts readily with alkenes or alkynes forming [2.1.1]bicyclic structures (Scheme 3, product A ). [ 47,50,51,55–57 ] Interestingly, with a small substituent at the alkyne such as R = H, the addition product B rearranges slowly upon thermal treatment to afford a [3.1.0]bicycle C , [ 58 ] which is not the observed for bulky substituents (e.g. R = Ph).…”
Section: Introductionmentioning
confidence: 99%